MO158: The Association of Left Ventricular Diastolic Dysfunction and Heart Failure in Patients with Chronic Kidney Disease. (3rd May 2022) - Babovic, Batric; Belada Babovic, Natasa; Radovic, Milan; Mihaljevic, Olgica; Gledovic, Branka; Mucic, Elvir; Radunovic, Danilo; Prelevic, Vladimir; Boskovic, Vasilije; Tomović, Filip; Usaku, Ilirjana; Gracanin Radovic, Danka
Abstract: BACKGROUND AND AIMS: Chronic kidney disease (CKD) has been linked with an increased risk of cardiovascular events, especially in dialysis population. According to literature data, in the patients with CKD heart function disturbances are twice as common as in the general population [1 ]. Bearing in the mind that left ventricular hypertrophy (and abnormal left ventricular relaxation) is considered to be one of the most important parameters for the occurrence of cardiovascular disease in CKD [2 ], the aim of our study was to evaluate the association of left ventricular diastolic dysfunction with heart failure in CKD patients. METHOD: The research was conducted as a prospective observational study which included 30 patients with CKD, stage III and IV according KDIGO [3 ], and left ventricular diastolic dysfunction, and 30 control subjects who also had left ventricular diastolic dysfunction but without CKD. Pulse-wave (PW) Doppler echocardiography in the apical four-chamber view and tissue Doppler imaging were performed to assess left ventricular function [4 ]. The measurements of mitral inflow by PW Doppler covered early (E-wave) and late (A-wave) diastolic feeling velocities, peak early diastolic velocity at the septal (e′septal ) and lateral (e′lateral ) mitral annular sites, and E/A ratio. RESULTS: A comparison of left ventricular function parameters between two groups of study participants indicated that left ventricular ejection fraction (0.57 ± 0.05% versus 0.61 ± 0.03%) was statistically reduced in CKD patients compared to control subjects ( P  < .001). Contrary, left ventricular mass index (119.8 ± 27.0 g/m 2 versus 100.8 ± 20.4 g/m 2 P  = .003) and interventricular septum thickness (11.8 ± 1.4 mm versus 10.8 ± 1.5 mm,   P  = .012) were significantly higher in the patients with CKD. There were no significant differences in values of left ventricular end-diastolic (53.7 ± 4.6 mm versus 54.2 ± 3.5 mm,   P  = .636) and left ventricular end-systolic (34.7 ± 4.5 mm versus 35.7 ± 2.3 mm,   P  = .265) dimension between CKD patients and controls. The mitral inflow imaging pointed to more pronounced left ventricular diastolic dysfunction in CKD patients than in the subjects without CKD: e′septal ( P  = .009) and e′lateral ( P  < .001) velocity. E/A ratio showed no markedly deviation between two study groups ( P  = .787). On the other hand, when we analysed the frequency of heart failure, it was noted that newly developed episodes of cardiac decompensation were more frequent in patients with CKD than in the control group (Chi square = 6.667, P  = .010). Regression analysis confirmed the predictive significance of left ventricular echosonographic characteristics on the occurrence of heart failure in patients with CKD (OR 1.56, 95% CI 1.11‒2.18, P  = .011 for left ventricular mass index; OR 1.68, 95% CI 1.01‒2.80, P  = .048 for e′). CONCLUSION: Heart failure is more common in patients with CKD than in patients with normal kidney function. There is a positive relationship between the presence of left ventricular diastolic dysfunction and the occurrence of heart failure in patients with CKD.